INTERHEMISPHERIC ASYMMETRY OF THE BRAIN IN PARKINSON’S DISEASE - Yvan Guan, Duo Zio (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
We found that in half of the cases, patients with Parkinson’s disease are characterized mainly by the right individual profile of functional interhemispheric asymmetry, and in a third of patients there is a right asymmetry profile, mixed and left asymmetry profiles are much less common. We were able to show that the individual profile of functional interhemispheric asymmetry predetermines the clinical lateralization of motor manifestations in Parkinson’s disease. At the same time, we also found that the combination of a certain individual functional profile of interhemispheric asymmetry with the clinical asymmetry of the disease determines the rate of progression of Parkinson’s disease. The individual profile of functional interhemispheric asymmetry, the onset side of the disease, and the type of life experience do not affect anxiety-depressive disorders in patients with Parkinson’s disease. Indicators of quality of life in patients with Parkinson’s disease depend on the variant combination of an individual profile of functional interhemispheric asymmetry and clinical lateralization of the disease. The relationship between the combination of the debut side of the disease and a certain individual profile with the localization of the generator of pathological activity according to the data of a computer electroencephalographic study in patients with Parkinson’s disease has been established.